Emerging rapidly growing nontuberculous mycobacteria: a retrospective analysis of pulmonary and extrapulmonary isolates and antimicrobial susceptibility - Singh, Puneeta; Malik, Shalabh; Lal, Vandana (International Journal of Research in Medical Sciences, 2026)
Introduction: Rapidly growing nontuberculous mycobacteria (RGM) account for nearly half of all recognized NTM species and are reported more frequently in Asia than in Western regions. Despite this, data describing RGM infections from North India remain sparse. We evaluated the incidence, species distribution, and antimicrobial susceptibility profiles of pulmonary and extrapulmonary RGM isolates from Delhi, North India. Methods: A total of 3,624 NTM isolates recovered from pulmonary and extrapulmonary specimens were analyzed. Species identification was performed using MALDI-TOF MS, and antimicrobial susceptibility testing was conducted by broth microdilution in accordance with American Thoracic Society/Infectious Diseases Society of America guidelines. This analysis is limited to culture-positive RGM isolates and does not differentiate colonization from clinically significant disease. Results: Among 26,475 mycobacterial isolates, 3,624 (12.1%) were identified as NTM, of which 2,115 (58.3%) were RGM. The Mycobacterium abscessus complex predominated (80.9%), followed by the M. fortuitum group (17.6%); other RGM species were infrequently isolated. RGM were recovered from both pulmonary and extrapulmonary specimens. Antimicrobial susceptibility testing demonstrated the highest in vitro activity for Amikacin, Clarithromycin, and Linezolid, with marked interspecies variability and frequent multidrug resistance, particularly among M. abscessus complex isolates. Conclusions: Despite India being highly endemic for tuberculosis, the epidemiology of NTM particularly RGM remains insufficiently characterized. The findings highlight substantial species diversity and high levels of antimicrobial resistance among RGM isolates in North India, including extensive antimicrobial resistance M. abscessus. These data underscore the importance of accurate species-level identification, routine susceptibility testing, and sustained regional surveillance to optimize management and monitor evolving resistance trends.